2021
DOI: 10.3390/nu13093217
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Recovery Effects of Resveratrol Supplementation on Exercise Performance and Muscle Damage following Acute Plyometric Exercise

Abstract: Plyometric exercise (PE) is an effective training method to increase muscle mass and strength. However, excessive or inappropriate conditions might cause exercise-induced muscle damage (EIMD). Resveratrol (RES) is a natural polyphenol plant antitoxin, which improves exercise performance, and exhibits anti-oxidation, anti-inflammatory, and anti-cancer effects. Therefore, this study investigated the effect of RES supplementation on the recovery of muscle damage, inflammation, soreness, muscle power, and anaerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Contrarily, other pre-clinical [ 54 , 55 , 56 , 57 , 58 ] or clinical studies [ 59 , 60 ] did not find any deleterious effect of resveratrol supplementation on exercise performance, independently of its effect as an ergogenic aid. Thus, in a dose-dependent manner, the administration of resveratrol in combination with several training programs (plyometric exercise, high-intensity cycling, resistance training, …) shows positive effects, such as a reduction in the decline in strength performance [ 59 ], a reduction in pain or damage indexes [ 59 ], a reduction in the inflammation induced by plyometric-exercise-induced muscle damage [ 59 ] or exercise-induced inflammation [ 60 ], or fatigue [ 56 , 58 ] markers, and it could accelerate recovery [ 59 ] or increase grip strength [ 55 , 56 , 58 ], contractile force [ 54 ], or aerobic performance [ 55 ].…”
Section: Resultsmentioning
confidence: 89%
“…Contrarily, other pre-clinical [ 54 , 55 , 56 , 57 , 58 ] or clinical studies [ 59 , 60 ] did not find any deleterious effect of resveratrol supplementation on exercise performance, independently of its effect as an ergogenic aid. Thus, in a dose-dependent manner, the administration of resveratrol in combination with several training programs (plyometric exercise, high-intensity cycling, resistance training, …) shows positive effects, such as a reduction in the decline in strength performance [ 59 ], a reduction in pain or damage indexes [ 59 ], a reduction in the inflammation induced by plyometric-exercise-induced muscle damage [ 59 ] or exercise-induced inflammation [ 60 ], or fatigue [ 56 , 58 ] markers, and it could accelerate recovery [ 59 ] or increase grip strength [ 55 , 56 , 58 ], contractile force [ 54 ], or aerobic performance [ 55 ].…”
Section: Resultsmentioning
confidence: 89%
“…We refer to the way in which EIMD was successfully induced in the past [ 32 , 34 ]. All subjects were asked to perform 100 maximal vertical jumps.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, they were instructed to squat until their knees were bent 90 degrees, then immediately jump as high as possible with maximum force. Each participant performed 3 replicates; we obtained CMJ data at the designated points and calibrated the instrument for each individual’s weight [ 34 ]. The measured parameters were rate of force development (RFD), relative peak force, and jump height.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, dietary supplements that relieve pain and discomfort after sports injuries and promote injury repair have fewer side effects than, for example, NSAIDs, and are more effective in improving physical fitness (17). Natural ingredients, such as curcumin, quercetin, and resveratrol, are a great treasure trove and have been found to be effective for sports injuries (18)(19)(20). Our previous studies have found that Rhodiola rosea as a natural supplement has a positive effect on exercise capacity and performance, reduces post-exercise pain and skeletal muscle injury, and enhances antioxidant capacity (21).…”
Section: Introductionmentioning
confidence: 99%